2014
DOI: 10.1128/iai.00022-14
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Functions of Hyaluronidase from Streptococcus agalactiae Are Enhanced Intracellular Survival and Inhibition of Proinflammatory Cytokine Expression

Abstract: Streptococcus agalactiae is the causative agent of septicemia and meningitis in fish. Previous studies have shown that hyaluronidase (Hyl) is an important virulence factor in many Gram-positive bacteria. To investigate the role of S. agalactiae Hyl during interaction with macrophages, we inactivated the gene encoding extracellular hyaluronidase, hylB, in a clinical Hyl ؉ isolate. The isogenic hylb mutant (⌬hylb) displayed reduced survival in macrophages compared to the wild type and stimulated a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 59 publications
7
61
0
Order By: Relevance
“…Andrey et al (156) showed that B indirectly represses tst transcription via a mechanism involving SarA and Agr. While hyaluronidase provides bacteria access to an abundant carbon source within host tissue (88), it is also speculated to play a direct role in pathogenesis by making host tissue more penetrable, although this notion has not been proven experimentally (157)(158)(159)(160). Supporting this hypothesis is the fact that a hysA mutant is attenuated in a mouse skin abscess model (86).…”
Section: B In Pathogenesissupporting
confidence: 53%
“…Andrey et al (156) showed that B indirectly represses tst transcription via a mechanism involving SarA and Agr. While hyaluronidase provides bacteria access to an abundant carbon source within host tissue (88), it is also speculated to play a direct role in pathogenesis by making host tissue more penetrable, although this notion has not been proven experimentally (157)(158)(159)(160). Supporting this hypothesis is the fact that a hysA mutant is attenuated in a mouse skin abscess model (86).…”
Section: B In Pathogenesissupporting
confidence: 53%
“…Thus, CodY could control biofilm dissemination in a nutrient-dependent manner and facilitate S. aureus survival when facing a resource-depleted environment (i.e., nutritional immunity [52]). In addition, multiple hyaluronidase-producing pathogens, such as S. pneumoniae, S. pyogenes, Streptococcus agalactiae, and Mycobacterium tuberculosis, have been shown to utilize HA as the sole carbon source (24,25,53,54). Although the ability of S. aureus to catabolize HA has not been demonstrated definitively (55), it is possible that HysAmediated liberation of N-acetylglucosamine-glucuronate disaccharides during biofilm dispersal serves as a carbon source available to planktonic cells invading host tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HysA from S. aureus and other Gram-positive pathogens (e.g., group A streptococci and S. agalactiae) possess greater enzymatic processivity and break down HA into disaccharide units (62). Inactivation of hyaluronidase in S. agalactiae elicits enhanced cytokine responses from both macrophage cultures and splenic homogenates following infectious challenge (54), suggesting that such catabolic end products may actually promote immune evasion. Given that within the context of S. aureus infection, polymeric HA is subject to both host-and pathogen-mediated degradation, further investigation will be needed to precisely define the immunoregulatory properties of HysA-derived disaccharides and their significance to the infective process.…”
Section: Discussionmentioning
confidence: 99%
“…The HylB protein encoded by the gene hylB is a hyaluronidase which cleaves hyaluronic acid, the main component of the extracellular matrix, contributing to the spread of GBS [14] [15].…”
Section: Introductionmentioning
confidence: 99%